Assessing psychosocial risk factors in children with Sickle Cell Disease - Nicole Frey; Julia E. LaMotte; Jillian R. Bouck; Lauren Fancher; Genese T. Parker; Allie Carter; Seethal A. Jacob (BMC Health Services Research)
Abstract Background Individuals with Sickle Cell Disease (SCD) are a minoritized and marginalized community that have disparate health outcomes as a result of systemic racism and disease-related stigma. The purpose of this study was to determine the psychosocial risk factors for families caring for children with SCD at a pediatric SCD center through use of the Psychosocial Assessment Tool (PAT), a validated caregiver-report screener. Methods The PAT was administered annually during routine clinical visits and scored by the SCD Social Worker to provide tailored resources to families. The PAT stratifies scores into 3 categories of psychosocial concern: Universal, Targeted, Clinical. PATs administered between September 2021-December 2022 were analyzed. Results Two hundred twenty-five PATs were included for analysis. Most caregivers identified as Black, single Women over 21 years old with a high school degree or more. The average patient age was 8.2 years (0–22 years). Sixty-seven percent of PATs fell into the Universal category. Dyads that scored in the Targeted or Clinical categories were more likely to report financial hardship, caregiver mental health concerns, and family stressors (p < 0.001). Nearly 50% of all families reported some form of financial difficulty, including almost 40% in the Universal category. Conclusions Universal implementation of a psychosocial risk screener identified financial challenges for many families, as well as caregiver burden and mental health concerns, allowing for timely resource support. However, overall risk for many of these families was categorized as Universal or low risk, indicating that distribution of resources and support cannot be based on PAT category alone.